PERSEPSI WISATAWAN TERHADAP PRODUK WISATA DI GEOPARK MERANGIN JAMB - , Nurlena, Prof. Dr. M. Baiquni, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Merangin Jambi Geopark (MJG) is on his way to be the member of Global Geopark Network (GGN). In this case, tourism development becomes an important aspect. Therefore, this study aims to analyze the perception of tourists as the main actor in tourism activities by using a quantitative-qualitative approach by which the data were collected from 85 respondents (sample) through questionnaires as well as from interviews and observation. The analysis results of various indicators for the touristsâ perception of tourism products in MJG showed that the geopark has a relatively high potential for geodiversity, biodiversity and cultural diversity, even some of them have been being developed into tourist attractions. In addition, out of 4 aspects of tourism products, only attraction which gets the highest positive perception percentage (82%) meaning that the attractions are interesting enough and deserved to satisfy the visitors. Tourist organizations/managers get positive perception of 58%, which indicates that visitors are quite satisfied, but they need some improvement. Meanwhile, amenities and accessibility have more negative perception which indicates that the government should pay more attention on these two aspects.